US Internationalization Faces the Recession - Green, Madeleine; Ferguson, Adelaide (International Higher Education, 2012)
U.S. higher education has been hard hit by the recession, and internationalization is no exception. This article focuses on campus responses to budgetary constraints among large public institutions, including staff reductions, intensified recruitment of international students, and expectations that senior internationalization officers (SIOs) will balance their budgets through income-generating activities. It also notes the apparent strengthening of the role of the SIO and concludes that commitment to internationalization seems to be holding up in face of hard times.